Experimental evidence of the quantitative relationship between the prokaryote ingestion rate and the food vacuole content in mixotrophic phytoflagellates. Issue 6 (15th October 2018) - Ballen‐Segura, Miguel; Catalan, Jordi; Felip, Marisol
Summary: The verification that many phytoflagellates ingest prokaryotes has changed the view of the microbial loop in aquatic ecosystems. Still, progress is limited because the phagotrophic activity is difficult to quantify in natural assemblages. Linking the food vacuole content in protist with the ingestion rate of prokaryotes would provide a crucial step forward. In this study, using the catalysed reporter deposition – fluorescence in situ hybridization protocol (CARD‐FISH), which allows the visualization of labelled prokaryotes inside protists without relying on incubation procedures, we experimentally relate the food vacuole content of prokaryotes ( V c ) to the population‐averaged ingestion rates ( I r ) estimated using bacteria‐size fluorescent microspheres. The two variables relate according to the equation I r = 7.52 Vc 0.9, which indicates a prokaryote half‐life of about 6 min in the protist vacuole. Five mixotrophic flagellate species from natural and culture populations were evaluated seven times during 24 h; they provided a broad range of average vacuole content (0.01 to 2.02 prokaryote protist −1 ) and ingestion rates (0.18 to 23 prokaryote protist −1 h −1 ). Consequently, the relationship found can be applied to quantify the mixotrophy activity in a large variety of field and experimental studies.